2020
DOI: 10.47187/perf.v2i22.54
|View full text |Cite
|
Sign up to set email alerts
|

Nuevas Fuentes De Antioxidantes Naturales: Caracterización De Compuestos Bioactivos en Cinco Frutos Nativos De Chile

Abstract: Diferentes berries de la zona centro y sur de Chile fueron analizados con el fin de buscar fuentes promisorias de polifenoles con clara actividad sobre la salud humana. Se estudiaron cinco bayas nativas: arrayan, frutilla blanca, murtilla y calafate, y un berry tradicional (uva tintorera). Se determinó in vitro sus propiedades antioxidantes según el ensayo de polifenoles totales de Folin Ciocalteu, antocianinas por pH diferencial, capacidad antioxidante por medición de capacidad de reducción del radical libre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
3
0
3
Order By: Relevance
“…As we noticed, this is a result of thermal amplitude observed that year, since low temperatures for long periods cause small berries to be produced by plants [37]. Ranges of pH 3.6-3.7 are in agreement with the last year's publication [21] while in acidity and soluble solids concerning 2% and 27.2 • Brix, data showed the highest values in the first year of this study. That year stands out because it presents lower temperature and higher radiation favoring stress in plants.…”
Section: Physicochemical Parameterssupporting
confidence: 83%
See 1 more Smart Citation
“…As we noticed, this is a result of thermal amplitude observed that year, since low temperatures for long periods cause small berries to be produced by plants [37]. Ranges of pH 3.6-3.7 are in agreement with the last year's publication [21] while in acidity and soluble solids concerning 2% and 27.2 • Brix, data showed the highest values in the first year of this study. That year stands out because it presents lower temperature and higher radiation favoring stress in plants.…”
Section: Physicochemical Parameterssupporting
confidence: 83%
“…The soluble solids were determined using a SPER SCIENTIFIC series 300,010 refractometer (0.2% Resolution, ±0.2% Accuracy) (Scottsdale, AZ, USA), expressing the results in • Brix. Acidity was determined by titration with NaOH 0.1 M from 0.5 g of crushed sample diluted in 150 mL of distilled water [21]. The color parameters CIEL*a* b*, as well as C* (Color saturation) and • H (Hue angle, tan −1 (b/a) were measured as previously described [22], with a PCE-CSM 2 colorimeter (Hunter Lab ® , Murnau am Staffelsee, Germany).…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
“…Después se volvió a sonicar por 1 hora para proceder a centrifugar a 3500 rpm durante 15 min, con un posterior filtrado (Romero et al, 2019).…”
Section: Extracción De Los Analitosunclassified
“…The DPPH antioxidant capacity was performed after Romero-Román et al [44] by diluting the extract and incorporating DPPH solution, which was shaken and kept in the dark for 1 h, at room temperature, and then spectrophotometer readings were taken at 515 nm. Subsequently, a standard curve of Trolox was carried out [45].…”
Section: Fruit Yield and Chemical Compoundsmentioning
confidence: 99%